Safety of COVID-19 vaccines - B. K. Romanov (Безопасность и риск фармакотерапии)
By June 1, 2022, there were 38 prophylactic COVID-19 vaccines approved in 197 countries around the world. The ongoing approval of new vaccines and the accumulation of more than a year's worth of data on their use give particular importance to the consolidation and analysis of information on the safety of such vaccines.The aim of study was to analyse the information on adverse events after immunisation (AEFIs) with coronavirus vaccines in the individual case safety reports entered into the VigiBase database by June 1, 2022.Materials and methods: the author analysed safety reports retrieved from VigiBase through the VigiLyze interface in the expert access mode. The search was carried out using the generic keyword “Covid-19 vaccine” in combination with the trade names of all 38 coronavirus vaccines.Results: the article presents consolidated information on the number and content of the safety reports on COVID-19 vaccines. The author noted that the reports were characterised by a high level of information completeness and quality, which could be due to the fact that the main reporters were the countries with developed pharmacovigilance systems. The analysis of patient complaints showed that the reported symptoms of AEFIs coincided with the manifestations of side effects of the vaccines included in the package leaflets. The author carried out a review of the cases of serious AEFIs and the cases of adverse events of special interest requiring additional monitoring after immunisation. It revealed a positive correlation of individual vaccines with the cases of somnolence in post-COVID-19 patients.Conclusions: the data obtained on the global safety of coronavirus vaccines may be of practical interest to doctors, researchers, developers, and healthcare regulators.